Artificial Intelligence and Academic Journals: For Better and for Worse - Ivan Lapuente Garrido (BAR: Brazilian Administration Review, 2023)
This editorial summarizes a talk presented during the 47th EnANPAD Annual Meeting in São Paulo, Brazil, exploring the role of artificial intelligence (AI) in academic journals. It highlights the impact perspectives of AI, recognizing its effects in various social and academic areas. Although the effects are extensive and their full ramifications are unknown and uncertain, the editorial highlights elements of opportunities and threats of this impact, as well as some ways to mitigate the impact. Journals could become smarter and more accessible with AI, providing a personalized experience for researchers and readers. However, significant challenges, such as the risk of inequality between journals with and without AI capabilities, are also highlighted. To seize opportunities and mitigate challenges, the author advocates for investment in AI, the creation of clear editorial guidelines, and an institutional commitment to responsibility and ethics.